2017
DOI: 10.1515/amm-2017-0259
|View full text |Cite
|
Sign up to set email alerts
|

The Precipitation Processes and Mechanical Properties of Aged Inconel 718 Alloy After Annealing

Abstract: Inconel 718 is a precipitation hardenable nickel-iron based superalloy. It has exceptionally high strength and ductility compared to other metallic materials. This is due to intense precipitation of the γ' and γ" strengthening phases in the temperature range 650-850°C. The main purpose of the authors was to analyze the aging process in Inconel 718 obtained in accordance with AMS 5596, and its effect on the mechanical properties. Tensile and hardness tests were used to evaluate the mechanical properties, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The reason behind selecting these two cross-sections was to understand the presence of any inhomogeneity in microstructure (mainly in terms of grain size) from the centre to the periphery, as it was normally expected due to the difference in cooling rate, following billet forging and after solution annealing, from the centre to the periphery of any bulk cylinder. [14] observed formation of a stable phase when exposed to temperatures above 650°C and Maj et al [15] reported direct formation of phase from the γ matrix in the temperature range of 900°C -950°C. In addition to this, Candioto et al [12], Kishan and Nagarajan [14] and Maj et al [15] pointed out that the nucleation of phase was mainly occurred at the grain boundaries leading to heterogeneous weakening of the material, low ductility, reduction in the maximum elongation during tensile test, an increase in brittleness and hindrance in the grain growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason behind selecting these two cross-sections was to understand the presence of any inhomogeneity in microstructure (mainly in terms of grain size) from the centre to the periphery, as it was normally expected due to the difference in cooling rate, following billet forging and after solution annealing, from the centre to the periphery of any bulk cylinder. [14] observed formation of a stable phase when exposed to temperatures above 650°C and Maj et al [15] reported direct formation of phase from the γ matrix in the temperature range of 900°C -950°C. In addition to this, Candioto et al [12], Kishan and Nagarajan [14] and Maj et al [15] pointed out that the nucleation of phase was mainly occurred at the grain boundaries leading to heterogeneous weakening of the material, low ductility, reduction in the maximum elongation during tensile test, an increase in brittleness and hindrance in the grain growth.…”
Section: Methodsmentioning
confidence: 99%
“…[14] observed formation of a stable phase when exposed to temperatures above 650°C and Maj et al [15] reported direct formation of phase from the γ matrix in the temperature range of 900°C -950°C. In addition to this, Candioto et al [12], Kishan and Nagarajan [14] and Maj et al [15] pointed out that the nucleation of phase was mainly occurred at the grain boundaries leading to heterogeneous weakening of the material, low ductility, reduction in the maximum elongation during tensile test, an increase in brittleness and hindrance in the grain growth. Thus phase formation was considered detrimental for cold rotary forging operation.…”
Section: Methodsmentioning
confidence: 99%
“…The second important aspect that has to be taken into consideration is the fact that exposing of Inconel alloys to the long-term annealing process may have consequences in the formation of precipitates in their microstructure (e.g. carbides, γ" and δ phases) [34][35][36][37]. Although, the classic heat treatments of the clad-plates are not long enough to cause the precipitation processes in Inconel alloys, the severe plastic deformation which affects the material in the joint area influence the kinetic of precipitating significantly promotes quicker formation of precipitates [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Inconel alloys display a tendency to form precipitates (e.g. carbides, γ′, γ″ and δ phases) upon long-term exposure to high temperature [34][35][36][37]. Importantly, plastic deformation of Inconel alloys exerts a considerable impact on the kinetics of precipitate formation, as it promotes their quicker development [38][39][40].…”
Section: Introductionmentioning
confidence: 99%